'A room of one's own': remote learning among Palestinian-Arab female students in the Israeli periphery following the COVID-19 crisis. Issue 3 (3rd April 2022) - Meler, Tal
ABSTRACT: The COVID-19 pandemic has had a significant impact on the health, wellbeing, learning, housing and living arrangements, work and family life of students worldwide. This study analysed the effect of the implementation of remote learning on Palestinian-Arab female students from a college in Israeli periphery. This article aims to address the perpetuation of inequalities vis-á-vis gender-ethno-national-civil status on online learning, focussing on family relations and infrastructure. My qualitative study of Palestinian-Arab female undergraduates during the crisis shows that students were forced to study in a shared family space because they did not have their own room and sometimes shared equipment. Furthermore, they were drawn into family obligations, which reinforced their traditional gender role. The data indicate that these circumstances impair their ability to study. The study sheds light on the role of gender family relations in barriers to persistent devotion to higher education and success in attaining an undergraduate degree.